2018
DOI: 10.3892/ijo.2018.4482
|View full text |Cite|
|
Sign up to set email alerts
|

LRIG2 promotes the proliferation and cell cycle progression of glioblastoma cells in vitro and in vivo through enhancing PDGFRβ signaling

Abstract: The leucine-rich repeats and immunoglobulin-like domains (LRIG) gene family, comprising LRIG1, 2 and 3, encodes integral membrane proteins. It has been well established that LRIG1 negatively regulates multiple growth factor signaling pathways and is considered to be a tumor suppressor; however, the biological functions of LRIG2 remain largely unexplored. It was previously demonstrated that LRIG2 positively regulates epidermal growth factor receptor (EGFR) signaling, the most common aberrant receptor tyrosine k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…LRIG2 expression correlates with poor prognosis in SCC of the cervix and uterus, which show increased LRIG2 RNA levels (Hedman et al , ). It has also been shown that LRIG2 promotes EGFR signaling as a positive feedback loop in glioblastoma cells, supporting the hypothesis that LRIG2 is acting as an oncoprotein (Wang et al , ; Xiao et al , ; ). Importantly, although it is known that LRIG proteins can promote and suppress tumor growth in a tissue‐specific manner (Hedman and Henriksson, ), the molecular mechanisms and their impact on tumorigenesis in the skin are mostly unknown.…”
Section: Introductionmentioning
confidence: 53%
“…LRIG2 expression correlates with poor prognosis in SCC of the cervix and uterus, which show increased LRIG2 RNA levels (Hedman et al , ). It has also been shown that LRIG2 promotes EGFR signaling as a positive feedback loop in glioblastoma cells, supporting the hypothesis that LRIG2 is acting as an oncoprotein (Wang et al , ; Xiao et al , ; ). Importantly, although it is known that LRIG proteins can promote and suppress tumor growth in a tissue‐specific manner (Hedman and Henriksson, ), the molecular mechanisms and their impact on tumorigenesis in the skin are mostly unknown.…”
Section: Introductionmentioning
confidence: 53%
“…LRIG1, negatively regulates several receptor tyrosine kinase (RTK) signaling pathways and is associated with a better prognosis in many cancers (710). LRIG2 acts as a tumor promoter, stimulating proliferation and inhibiting apoptosis of glioma cells (11, 12). Several studies have shown that soluble LRIG1 (sLRIG1) and soluble LRIG2 (sLRIG2) have similar functions as their corresponding full-length proteins (11, 13, 14).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, an interaction with heparanase-1 is possible because this protein is also detected in pelvic ganglia ( Stuart et al, 2015 ) and, at least in rat phaeochromocytoma cells, heparanase-1 modulates neuritogenesis ( Cui et al, 2011 ). Of note, cell biology experiments implicate LRIG2 in axon guidance ( van Erp et al, 2015 ) and in controlling cell turnover in neural tumour cells ( Xiao et al, 2018 ). Further experiments are now required to determine the possible effects of LRIG2 on bladder nerve precursor cells.…”
Section: Discussionmentioning
confidence: 99%